Genome mining of Lactiplantibacillus plantarum PA21: insights into its antimicrobial potential - Isaac, Sharleen Livina; Abdul Malek, Ahmad Zuhairi; Hazif, Nurul Syafika; Roslan, Farah Syahrain; Mohd Hashim, Amalia; Song, Adelene Ai-Lian; Abdul Rahim, Raha; Wan Nur Ismah, Wan Ahmad Kamil (BioMed Central, 2024)
Background: The dramatic increase of antimicrobial resistance in the healthcare realm has become inexorably linked to the abuse of antibiotics over the years. Therefore, this study seeks to identify potential postbiotic metabolites derived from lactic acid bacteria such as Lactiplantibacillus plantarum that could exhibit antimicrobial properties against multi-drug resistant pathogens. Results: In the present work, the genome sequence of Lactiplantibacillus plantarum PA21 consisting of three contigs was assembled to a size of 3,218,706 bp. Phylogenomic analysis and average nucleotide identity (ANI) revealed L. plantarum PA21 is closely related to genomes isolated from diverse niches such as dairy products, food, and animals. Genome mining through the BAGEL4 and antiSMASH database revealed four bacteriocins in a single cluster and four regions of biosynthetic gene clusters responsible for the production of bioactive compounds. The potential probiotic genes indirectly responsible for postbiotic metabolites production were also identified. Additionally, in vitro studies showed that the L. plantarum PA21 cell-free supernatant exhibited antimicrobial activity against all nine methicillin-resistant Staphylococcus aureus (MRSA) and three out of 13 Klebsiella pneumoniae clinical isolates tested. Conclusion: Results in this study demonstrates that L. plantarum PA21 postbiotic metabolites is a prolific source of antimicrobials against multi-drug resistant pathogens with potential antimicrobial properties.